Aging promotes an increase in mitochondrial fragmentation in astrocytes - Araujo, Ana Paula Bergamo; Vargas, Gabriele; Hayashide, Lívia de Sá; Matias, Isadora; Andrade, Cherley Borba Vieira; de Carvalho, Jorge José; Gomes, Flávia Carvalho Alcantara; Diniz, Luan Pereira (Frontiers in Cellular Neuroscience, 2024)
Brain aging involves a complex interplay of cellular and molecular changes, including metabolic alterations and the accumulation of senescent cells. These changes often manifest as dysregulation in glucose metabolism and mitochondrial function, leading to reduced energy production, increased oxidative stress, and mitochondrial dysfunction—key contributors to age-related neurodegenerative diseases. In this study, we used two experimental models: young (3-4 months) and aged (over 18 months) mice, as well as cultures of senescent and control mouse astrocytes. We found that astrocytes and neurons from aged animals exhibited a significant reduction in mitochondrial content, accompanied by a decrease in mitochondrial biogenesis. In cultured senescent astrocytes, we observed reduced mitochondrial membrane potential and increased mitochondrial fragmentation. qPCR and immunocytochemistry analyses revealed a 68% increase in fusion-related proteins (mitofusin 1 and 2) and a 10-fold rise in DRP1, a key regulator of fission, highlighting increased mitochondrial fragmentation. Furthermore, transmission electron microscopy showed a reduction in perimeter, area, and length-to-diameter ratio of mitochondria in astrocytes from aged mice, corroborated by elevated DRP1 phosphorylation in astrocytes of the cerebral cortex. Our findings provide novel evidence of increased mitochondrial fragmentation in astrocytes from aged animals, offering new insights into the mechanisms driving astrocytic metabolic dysfunction and mitochondrial dysregulation in brain aging.